Persepsi Wisatawan Lanjut Usia Pada Fasilitas Akomodasi Dan Aktivitas Pariwisata Bernuansa Seni Budaya Di Desa Sanur - Yayu Indrawati (Institut Seni Indonesia Denpasar, 2009)
The aim of this research is to identify elder tourist perception toward accommodation facilities and tourism activities from art and cultural atmosphere point of view in Sanur Village. This research uses various approaches such as social and cultural, social exchange theory. This study took 50 (fifty) respondents, and they were used as sample using “proportional stratified random sampling”. Respondents were taken from elder tourist aged above 60 (sixty) years old comes from Australia, Nederland, German, United Kingdom and Japan. Data are taken by observation, interview, questioner and documentation. Silver age tourist’s perception is analyzed by Likert Scale and employed descriptive analysis method. The study shows that generally silver age tourist perception toward accommodation facilities is positive with average score 89.07%. Besides accommodation facilities it is also has activities related to fulfillment of physical need such as attending cultural events, exercises, hobbies and leisure.